1994
DOI: 10.1111/j.1365-3083.1994.tb03363.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of CD4+ T Cells Lacking Thy‐1 in Murine Retrovirus‐Induced Immunodeficiency Syndrome (MAIDS)

Abstract: Increased numbers of CD4+ Thy‐1 cells have been described in the spleen (SP) of mice with retrovirusinduced immunodeliciency (MAIDS). Since this phenotypic abnormality might have considerable functional importance, the expansion of the CD4+ Thy‐1 subset in MAIDS was characterized further. CD4+ Thy‐1− and Thy‐1+ T‐cell is from infected mice expressed similar densities of CD3 and TCR γ/β. In contrast, the Thy‐I− subset was uniformly CD44hi, even early in the disease when part of Thy‐I+ cells were still CD4410. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A large proportion of CD4 + T cells is characterized by an unusual CD90.2 (Thy-1.2)-negative phenotype in LP-BM5-infected mice compared with uninfected controls (42,43) (Fig. 7A, middle and left panels).…”
Section: Development Of Maids Phenotypic Characteristics Is Inhibitedmentioning
confidence: 99%
“…A large proportion of CD4 + T cells is characterized by an unusual CD90.2 (Thy-1.2)-negative phenotype in LP-BM5-infected mice compared with uninfected controls (42,43) (Fig. 7A, middle and left panels).…”
Section: Development Of Maids Phenotypic Characteristics Is Inhibitedmentioning
confidence: 99%
“…The role of the CD4 + Thy-1 ¹ phenotype is also intriguing. We have previously demonstrated that CD4 + Thy-1 ¹ T cells which expand in MAIDS originate from activated CD4 + Thy-1 + T cells rather than from the expansion of the CD4 + Thy-1 ¹ T cells from normal mice [7]. In addition, we have demonstrated impaired calcium fluxes in CD4 + Thy-1 ¹ T cells isolated from the LN of normal mice [31].…”
Section: Discussionmentioning
confidence: 78%
“…Using propidium iodide (PI) staining, we have previously compared the proliferating fraction of CD4 + T cells in PP versus LN during MAIDS [7]. Although higher than in the control mice, the proliferating fraction (S and G 2 + M) of CD4 + T cells was significantly lower in PP than in spleen or LN of the infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…MAIDS is characterized by the dramatic expansion of a CD4 + T‐cell subset with an unusual CD90 ‐ phenotype (9, 10). In view of previous reports showing that CD4 + CD90 ‐ T cells play an important role in the pathogenesis of the syndrome (41), we measured cAMP levels in this subset and compared it with levels in the CD90 + counterpart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to what is observed in the classical anergization models (engagement of the T‐cell receptor [TCR] in the absence of costimulation), exogenous interleukin 2 (IL‐2) fails to restore the proliferative responses of T cells from infected mice (8), suggesting the existence of a defect in the IL‐2 receptor signal transduction pathway. A large proportion of CD4 + T cells (but not CD8 + T cells) of infected mice are also characterized by an unusual CD90 (Thy‐1)‐negative phenotype (9, 10). It is unclear if the absence of membrane CD90 is due to a shedding process related to the cleavage of the glycosylphosphatidylinositol (GPI) anchor or if the protein is down‐regulated at the mRNA level.…”
mentioning
confidence: 99%